PARAMETER OPTIMIZATION OF DRILL PIPE FOR SPIRAL DRILLING MACHINE BASED ON FINITE ELEMENT METHOD - YU Ning; TIAN LiYong; SUN JuTao (Jixie qiangdu)
In order to improve the strength and life of the spiral drilling machine,and reduce the weight of the drill pipe,it took the spiral drill pipe of the spiral drilling machine as the research object. On the condition of meeting the strength requirement,it selected the weight of the drill pipe to be the lightest as the optimization goal. The solid optimization model was established in the software of Pro/E. The strength analysis was proceeded in the software of ANSYS Workbench based on finite element method,as the result it selected the thickness of the drill pipe and blade,height,helix angle as the optimizing parameters by observing the stress nephogram to optimize the structure parameters of the drill pipe. The result indicates that the strength of the spiral drilling machine has improved obviously,the stress is reduced by 15. 8% and the weight is reduced by6. 4%. The life of the drill pipe has been extended.